(untitled) (Italian Journal of Public Health, 2010)
Background: Ice cream and cream-based pastries are an excellent media for the growth of pathogenic microorganisms. Foods that are prepared without due respect to the rules of food hygiene can carry microorganisms and/or toxins and could be responsible of toxinfections. The main objective of this study was to obtain an overall picture of the hygiene/sanitation conditions found in businesses that produce hand-made pastries and/or ice cream in Naples, Italy. Methods: We inspected 34 businesses to assess the following aspects: hygiene/sanitation conditions of the work area and equipment, implementation of good food hygiene principles, evaluation of HACCP plans, licensing/authorization, quality control and sampling protocols, as well as systems for ensuring food traceability. In 28 of the businesses, samples (environment, foods, workers) were collected for microbiological analysis. Results: Sanctions were issued for nonconformities in 8 businesses (23.5%), and 25 businesses (73.5%) received warnings with orders to correct minor nonconformities (inadequate documentation of compliance with current regulations, incorrect implementation of the quality-control protocol) within specified time periods. Microbiological analyses revealed irregularities in 24/28 businesses (85.7%), and 138 of the 280 samples collected displayed contamination levels exceeding the limits adopted for this study (49.3%). In particular, 80% of the surfaces sampled and 23.8% of the hand swabs collected were shown to be contaminated. All food samples collected met the process-hygiene and food-safety standards prescribed by the European Community. Results obtained were statistically significant (p < 0.05). Conclusions: Our experience of food safety surveillance system indicates that Neapolitan food business operators involved in the production of hand-made ice cream or pastries do not fully understand the importance of the general preventive measures such as Good Hygienic Practices, Good Manufacturing Practice and Hazard Analysis Critical Control Point Codex requirements for providing consumers with safe, high-quality food products.